Classification of happiness in North Kalimantan using decision tree-based CHAID - Veriyanto, Andika; Giselle, Junezarra Thie Dea (Majalah Ilmiah Matematika dan Statistika, 2023)
The concept of welfare is closely related to economic development. The 2021 happiness index in Indonesia shows 5 provinces with the highest index have a GRDP that tends to be low. This study aims to examine the factors that influence happiness in North Kalimantan as the youngest province, which, according to the SPTK 2021, has the second-highest happiness index. The study employs a quantitative method as well as inferential analysis with a decision tree based CHAID to classify happiness. This method is advantageous since it can handle both categorical and continuous variables, as well as data that is not regularly distributed. The happiness level is the dependent variable in this study, with 19 independent variables indicating various factors such as life satisfaction, affect, and eudaimonia. According to the report, 70.2 percent of households in North Kalimantan are in the happy category. According to the findings of this study, the majority of happy households are experiencing pleasure and satisfied with their income. In households where they lack of pleasure, there are other factors that explain happiness such as job satisfaction and not feeling stressed. The accuracy from the CHAID model is 78.85 percent, indicating the model is fit to classify happiness. Keywords: Happiness index, CHAID, North Kalimantan, SPTK.MSC2020: 62C86